Etnomatematika Aplikasi Bentuk Bangun Ruang Geometri pada Masjid Astana Sultan Hadlirin - Siti Munawaroh, Dian Naila Apriyanti; Nur Malasari, Putri (Journal of Mathematics Learning Innovation, 2023)
This research was conducted to look for geometric elements in the Astana Sultan Hadlirin Mosque building. This research took place at the Sultan Hadlirin Mosque, Mantingan Village, Tahunan District, Jepara, Central Java. This research uses qualitative research methods using an ethnographic approach. The data collected was carried out through the observation process, documentation process and interview process. Human instruments and field notes are the instruments used by researchers in this research. The data analysis carried out by the researcher was by shrinking/reducing the data, interpreting the data from the results of the data reduction, and finally presenting the data results. From this research, results showed that several ethnomathematics concepts were found in mosques in the form of geometric elements including blocks, tubes, cubes, prisms, rectangles, trapezoids, triangles, squares, hexagons and circles. The results of the research that has been carried out are geometric elements found in the Sultan Hadlirin Mantingan Mosque which can be used as a learning reference in understanding the concept of local cultural geometry.